18FDG SUV in the primary tumor and lymph node metastases is not predictive for development of distant metastases in high risk head and neck cancer patients. Issue 5 (May 2015) - Meeuwis, Jasmijn; Hoekstra, Otto S.; Witte, Birgit I.; Boellaard, Ronald; Leemans, C. René; de Bree, Remco
Summary Background Pretreatment screening on distant metastases is particularly useful in head and neck squamous cell carcinoma (HNSCC) patients with high risk factors. Methods In a retrospective study of 88 patients with previously identified clinical high risk factors the predictive value of standardized uptake value (SUV) of 18F-fluorodeoxyglucose (FDG) in the primary tumor and in the lymph node metastases for the development of distant metastases was examined. Different SUVs corrected for plasma glucose levels and body mass index were calculated and analysed in different patient groups: all patients (n = 88), patients with a follow up >6 months (n = 73), not previously treated patients (n = 51) and not previously treated patients with a follow up >6 months (n = 40). Results Twenty-four of the 88 (27%) high risk HNSCC patients were diagnosed with distant metastases during screening and follow up. No correlation was found between different SUVs of the primary tumor and lymph nodes metastases and the development of distant metastases. Conclusion SUVs of primary tumor and lymph node on FDG-PET are not predictive for distant metastases in a (selected) group of patients with already high risk factors for distant metastases.